Overcoming uncertainty and barriers to adoption of Blue-Green Infrastructure for urban flood risk management - Thorne, C.R.; Lawson, E.C.; Ozawa, C.; Hamlin, S.L.; Smith, L.A. (Wiley, 2015)
Blue-Green Infrastructure (BGI) and Sustainable Drainage Systems (SuDS) are increasingly recognised as vital components of urban flood risk management. However, uncertainty regarding their hydrologic performance and lack of confidence concerning their public acceptability create concerns and challenges that limit their widespread adoption. This paper investigates barriers to implementation of BGI in Portland, Oregon, using the Relevant Dominant Uncertainty (RDU) approach. Two types of RDU are identified: scientific RDU’s related to physical processes that affect infrastructure performance and service provision, and socio-political RDU’s that reflect a lack of confidence in socio-political structures and public preferences for BGI. We find that socio-political RDU’s currently exert the strongest negative influences on BGI decision making in Portland. We conclude that identification and management of both biophysical and socio-political uncertainties are essential to broadening the implementation of BGI and sustainable urban flood risk management solutions that are practical, scientifically sound, and supported by local stakeholders.